2011
DOI: 10.5194/aab-54-280-2011
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA and protein expression of ruminal MCT1 is increased by feeding a mixed hay/concentrate diet compared with hay <i>ad libitum</i> diet (Short Communication)

Abstract: In this study the protein and mRNA expression of Monocarboxylate transporter 1 (MCT1) was evaluated in rumen epithelial cells (REC) obtained from sheep fed hay ad libitum (control, h diet, n=4) or a mixed hay/concentrate diet (h/c diet, n=4) for two weeks. REC were isolated via fractionated trypsination and three groups consisting of fractions 3 to 5=G1, fractions 6 to 8=G2, and fractions 9 and 10=G3 were formed. Using an anti-basal cytokeratin antibody and flow cytometric analysis, the proportion of REC origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…One possible explanation for the observed change is that the SCFA transport system of epithelial cells was enhanced by feeding additional concentrate. Kuzinski and Röntgen (2011) reported that the rumen epithelium of sheep fed additional concentrate had increased MCT1 expression. Similarly, a report in calves showed that the gene expression of DRA was upregulated by concentrate feeding (Connor et al, 2010).…”
Section: Effects Of Diet On the Expression Of Genes Related To Scfa Amentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for the observed change is that the SCFA transport system of epithelial cells was enhanced by feeding additional concentrate. Kuzinski and Röntgen (2011) reported that the rumen epithelium of sheep fed additional concentrate had increased MCT1 expression. Similarly, a report in calves showed that the gene expression of DRA was upregulated by concentrate feeding (Connor et al, 2010).…”
Section: Effects Of Diet On the Expression Of Genes Related To Scfa Amentioning
confidence: 99%
“…During the last decade, a surge of studies were done to determine dietary effects on the transcription changes in proteins involved in SCFA absorption (Penner et al, 2009;Kuzinski and Röntgen, 2011;Steele et al, 2011); however, most of those studies looked for individual SCFA transporter genes without further investigation into the influencing factors. The results of previous studies showed that luminal factors, especially SCFA and pH, can work as the modulators of gene transcription (DeCastro et al, 2005;Li and Li, 2006;Yang et al, 2012).…”
Section: Effects Of Scfa and Ph On The Expression Of Genes Related Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation processes include morphological transformations, such as alterations of the rumen epithelium papillae number and size (44). In addition, changes occur in the metabolic properties of rumen epithelial cells (REC) (3) and the expression and activity of cellular transport proteins (26,43,44).Ruminal transport processes are known to be energized by a highly expressed Na ϩ /K ϩ -ATPase, and modulation of the pump expression and activity by concentrate feeding and by forage types, inducing different rumen fermentation patterns, have been observed (24,25). In addition to the Na ϩ /K ϩ -ATPase, the existence of functional vacuolar-type H ϩ -ATPases (vH ϩ -ATPase) in REC has been shown by our group (1, 9).…”
mentioning
confidence: 99%
“…The adaptation processes include morphological transformations, such as alterations of the rumen epithelium papillae number and size (44). In addition, changes occur in the metabolic properties of rumen epithelial cells (REC) (3) and the expression and activity of cellular transport proteins (26,43,44).…”
mentioning
confidence: 99%